Perancangan Website Dalam Mendukung Digitalisasi Penjualan Pada Umkm Hallo Kopi - Annisa Amanda; Nurul Iffah; Sonia Aisyah Efendi; Novadilastri .; Sularno . (CV. ITTC INDONESIA, 2026)
The advancement of information technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to shift from conventional sales models to digital platforms. Hallo Kopi, a culinary MSME in Batusangkar City, West Sumatra, which operates a physical outlet (coffee shop) as well as a mobile unit using an electric bicycle cart, requires an integrated website design as a digital sales medium. This study aims to design a website that supports the sales digitalization process of Hallo Kopi, identify website features and functions needed to support transactions, and analyze its potential impact on business sales performance. The research employed a descriptive qualitative approach through a case study, with data collection techniques including system requirements observation, owner interviews, and documentation. The results yield a website design for Hallo Kopi that functions as a digital product catalog as well as an online ordering medium, extending market reach for both the physical outlet and mobile cart operations. This sales digitalization design is directed to improve consumer access, accelerate transaction processes, and strengthen digital brand identity. This research is expected to serve as a reference in modeling and implementing website-based sales digitalization for similar MSMEs.